Transitional Space In Tertiary Institutions As Informal Learning Space Towards 21St Century Education - Velusamy, Ramu (2022)
Undeniably, industrial revolution 4.0 and Covid-19 pandemic have wedged education system globally. The expansion and evolution of ICT in education evolution led to present-day learning theory called connectivism learning theory. Therefore, education institutions should choose to transform their course of action from the conventional norms to an already seemingly positive alternative of embracing online learning and informal learning. Online learning and informal learning occur with significant challenges, namely, technology access as the primary indicator of online readiness. Accordingly, an opposite informal learning space is compulsory to uphold the nature of this online learning which is more to informal learning or non-face to face learning. The effectiveness of the contemporary physical learning environment in higher education is questionable. A conducive and favorable learning space turns into a decisive issue globally. Hence, this research aims to determine learners’ perceptiveness and learners’ preferences attributes across three types of informal learning space. Furthermore, the relationship between informal learning space preferences attributes and three types of informal learning space needed to be evaluated. An exploratory sequential mixed method research design was employed to achieve these aims. This study involved diploma students from three Polytechnics.